Good Corporate Governance dan Kinerja Keuangan: Implikasi Moderasi Oleh Gender Diversity - Rista, Raharka Prismadifa; Andayani, Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research intends to investigate how Good Corporate Governance influences financial performance in companies and assess the moderating impact of gender diversity. This present study utilitized a quantitative design methodology that employed the panel data technique and Moderated Regression Analysis (MRA). The sample for the research includes companies in the basic materials sector that are listed on the Indonesia Stock Exchange from 2021 to 2023, totaling 24 companies and 72 observations. The information utilized is sourced from yearly reports and sustainability reports. The study results indicate that GCG does not have a meaningful impact on financial performance. Moreover, gender diversity in management has not been shown to notably influence the connection between Good Corporate Governance and financial performance. The analysis results suggest that a rise in the adoption of Good Corporate Governance, along with gender diversity, shows a positive trend toward enhancing financial performance, although the impact remains limited.